The Female Genital Mutilation Regulations In Indonesia: The International Law, Human Rights, and Islamic Law Perspectives - Lingga, Geofani; Najib, Shihaf Ismi Salman (Faculty of Law, Universitas Jambi, 2025)
This study analyzes the practice of female genital mutilation in Indonesia from the perspective of international law, human rights, and Islamic law. Using normative law research methods, this study reviews laws, case studies, and conducts regulatory comparisons on national law against international law, human rights, and Islamic law. This study found that national regulations such as Minister of Health Regulation No. 1636 of 2010 and Minister of Health Regulation No. 6 of 2014 have contained provisions regarding the practice of female genital mutilation, but have not provided comprehensive protection for women in the implementation of this practice. Meanwhile, from the perspective of international law, CEDAW and CRC affirm that female genital mutilation is a form of gender-based discrimination and a violation of children's rights. This study concludes that efforts to eliminate the practice of female genital mutilation require the role of the state in strengthening relevant regulations and increasing public awareness to provide better protection for women and girls.